(untitled) (Revista de Ciências Agroveterinárias, 2014)
In equine sports medicine, there is constant concern about poor performance in animals due to several organ dysfunctions, such as cardiovascular origin. Cardiovascular changes are the third most common cause, which can lead to intolerance to exercise or even sudden death. The electrocardiogram is a recording of electrical phenomena that arises during cardiac activity by electrocardiograph, which is considered a very useful diagnostic tool for the investigation of cardiac procedures. This review covers the use of electrocardiogram, its applicability and diagnosis of major arrhythmias found in equine species. Precise clinical significance of electrocardiographic changes during and after exercise is still unknown for this species. For these reasons, it is important to define electrocardiographic characteristics that change with training, allowing differentiation of animals that may have myocarditis or other pathological changes.